NAA60 facilitates LRRC8A- and LRRC8D-mediated platinum drug uptake - Widmer, Carmen Alexandra; Moyseos, Anna; Klebic, Ismar; Dettwiler, Martina; González-Fernández, Martín; Gogola, Ewa; Siffert, Myriam; Buchs, Natasha; Braga-Lagache, Sophie; Uldry, Anne-Christine; Jonkers, Jos; Heller, Manfred; et al. (Communications biology, 2025)
The platinum-based drugs cis- and carboplatin, which are crucial for treating cancers with DNA repair defects, like those caused by BRCA1/2 mutations, rely on the volume-regulated anion channel subunits LRRC8A and LRRC8D for about 50% of cellular drug uptake. Yet, the precise mechanisms of how LRRC8A and LRRC8D mediate this function are largely unknown. Here, we identify NAA60, an N-terminal acetyltransferase, which localizes to the Golgi apparatus to affect LRRC8A and LRRC8D function. Our data suggest that NAA60 acetylates the LRRC8A/D N-termini, and its loss decreases cis- and carboplatin uptake resulting in drug resistance of otherwise hypersensitive BRCA1;p53-deficient cells and tumors. Furthermore, we mimicked the absence of the neutralizing acetyl moiety that is observed after loss of NAA60 by introducing positively charged amino acids at the N-termini of LRRC8A/D, which indeed decreased cis- and carboplatin sensitivity. Our findings highlight the importance of N-terminal acetylation by NAA60 for effective platinum drug uptake, offering new insights into overcoming drug resistance. Genome-wide CRISPR/Cas9 screening identifies the N-terminal acetyltransferase NAA60 to facilitate cis- and carboplatin drug sensitivity, most likely by neutralizing Nt acetylation of the LRRC8A/D VRAC subunits regulating substrate permeability.